2023
DOI: 10.3389/fmicb.2022.1079056
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in situ ruminal straw fiber degradation and bacterial community between buffalo and Holstein fed with high-roughage diet

Abstract: Buffalo exhibits great efficiency in utilizing low-quality roughage, which can be due to the combined effect of host physiological feature and roughage diet fed. The present study was designed to compare the ruminal fiber degradation and the bacterial community attached to straws in buffalo and Holstein when fed with the same high-roughage diet using in situ ruminal incubation technique. Rice and wheat straws were selected as the incubation substrates and sampled at 0, 4, 12, 24, 48, 72, 120, and 216 h of incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…The ED of NDF and ADF in GS and AS were similar, but the b value of NDF in GS was 73.15%, which was significantly higher than that of AS (49.22%), and the degradation rate of ADF in GS (55.45%) was also significantly higher than that of AS (50.84%) at 72 h. This indicates that NDF in GS can be degraded slowly and continuously by rumen. These results are consistent with previous studies, which reported a negative correlation between rumen degradation and fiber content [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The ED of NDF and ADF in GS and AS were similar, but the b value of NDF in GS was 73.15%, which was significantly higher than that of AS (49.22%), and the degradation rate of ADF in GS (55.45%) was also significantly higher than that of AS (50.84%) at 72 h. This indicates that NDF in GS can be degraded slowly and continuously by rumen. These results are consistent with previous studies, which reported a negative correlation between rumen degradation and fiber content [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, the number of Prevotella in GS and AS decreased in different degrees in the later stage of degradation, which was consistent with the experimental results of Vahidi et al [ 54 ]. The relative abundance of Prevotella in GS was higher than that in AS, which may be due to the low fiber content in GS, and Prevotella tended to mobilize readily available nutrients (such as soluble sugars and proteins) [ 34 ]. Treponema and Ruminococcus are hydrolytic and acid-producing bacteria [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…2C), consistent with the distribution patterns seen in prokaryotic communities within the ruminant GIT 6 . Notably, GIT regions had greater variance (31.2%) S9), which aligns with rumen being the largest compartment in the ruminant GIT and hosting the highest bacterial populations 38 . Such distinct viral communities among GIT regions could be attributable to multiple factors, such as substrate availabilities and microbial metabolism 6 .…”
Section: Ruminant Viral Communities Are Diverse and Primarily Driven ...mentioning
confidence: 65%
“…Distinct forages demonstrate varied dry matter (DM) degradation rates upon rumen entry, with the microbial composition attached to particles differing across feeds [9]. However, Comprehensive knowledge about rumen bacterial diversity, especially concerning feeds rich in cellulose and hemicellulose, remains limited [10][11][12]. The genus Prevotella, notably dominant, plays a significant role in enzyme families associated with fiber degradation [13][14][15].…”
Section: Introductionmentioning
confidence: 99%